Lepus (Lepus) arcticus subsp. monstrabilis Nelson 1934 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Lepus (Lepus) arcticus subsp. monstrabilis Nelson 1934 Synonyms: Lepus (Lepus) arcticus subsp. hubbardi Handley 1952. Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Lagomorpha, pp. 185-211 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 196, DOI: 10.5281/zenodo.7316519